2022
DOI: 10.1002/aur.2712
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic and sex differences in cognitive profiles of autism spectrum disorder and attention‐deficit/hyperactivity disorder

Abstract: An increasing number of studies have shown that autism spectrum disorder (ASD) and attention‐deficit/hyperactivity disorder (ADHD) share symptoms and aetiologies. However, transdiagnostic comparisons between ASD and ADHD is complicated due to the sex differences within each condition. To clarify the similarities and differences in the cognitive functioning between ASD and ADHD, while considering potential sex differences, this study compared cognitive profiles assessed by the WAIS‐III between the four groups c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A previous study by Takeda et al (2020) attempted to identify differences in Wechsler Adult Intelligence Scale profiles between ADHD patients and healthy controls, but no significant group differences were found in Verbal intelligence quotient. However, a more recent study by Doi et al (2022) found that female ADHD patients had a lower Verbal intelligence quotient compared to males when characterizing the cognitive profile of ADHD and ASD.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study by Takeda et al (2020) attempted to identify differences in Wechsler Adult Intelligence Scale profiles between ADHD patients and healthy controls, but no significant group differences were found in Verbal intelligence quotient. However, a more recent study by Doi et al (2022) found that female ADHD patients had a lower Verbal intelligence quotient compared to males when characterizing the cognitive profile of ADHD and ASD.…”
Section: Methodsmentioning
confidence: 95%
“…Verbal intelligence quotient. However, a more recent study by Doi et al (2022) found that female ADHD patients had a lower Verbal intelligence quotient compared to males when characterizing the cognitive profile of ADHD and ASD.…”
Section: Languagementioning
confidence: 95%
“…Neurocognitive profiles are of clinical importance for individuals with neurodevelopmental disorders, as cognitive performance has been shown to relate to severity of communication and social difficulties (Demetriou et al, 2018; Leung et al, 2016; Oliveras‐Rentas et al, 2012) and repetitive behaviors (Mostert‐Kerckhoffs et al, 2015), can differentiate individuals with autism spectrum disorders (ASD) (Doi et al, 2022; Nader et al, 2015; Solomon et al, 2021), potentially predict behavioral challenges, and is often used to aid diagnoses (Nader et al, 2015). As such, classifying individuals based on neurocognitive profiles could provide a framework for uncovering genetic and neurobiological differences associated with autism phenotypes, allowing for improved diagnosis and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Neurocognitive profiles are of clinical importance for individuals with neurodevelopmental disorders, as cognitive performance has been shown to relate to severity of communication and social difficulties (Demetriou et al, 2018;Leung, Vogan, Powell, Anagnostou, & Taylor, 2016;Oliveras-Rentas, Kenworthy, Roberson, Martin, & Wallace, 2012) and repetitive behaviors (Mostert-Kerckhoffs, Staal, Houben, & de Jonge, 2015), can differentiate individuals with Autism Spectrum Disorders (ASD) (Doi, Kanai, & Ohta, 2022;Nader, Jelenic, & Soulières, 2015;Solomon et al, 2021), potentially predict behavioral challenges, and is often used to aid diagnoses (Nader et al, 2015). As such, classifying individuals based on neurocognitive profiles could provide a framework for uncovering genetic and neurobiological differences associated with autism phenotypes, allowing for improved diagnosis and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%